The Influence of Job Satisfaction and Work-Family Conflict on Turnover Intention of Female Nurses at XYZ Hospital, Bandung City - Hasna, Amira Aghniya; Hadiantini, Ratih; Simarmata, Harianto (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This study aims to determine the description of job satisfaction, Work Family Conflict and turnover intention and to find the magnitude of the influence of job satisfaction and Work Family Conflict on turnover intention in female nurses at XYZ Hospital, Bandung City, both partially and simultaneously. The method used is descriptive and verification with a quantitative approach. The population used is all female nurses at XYZ Hospital, Bandung City, totaling 97 respondents using a non-probability sampling technique, namely a saturated sampling technique. Based on the results of the determination test, it was found that job satisfaction had a 12.4% effect on turnover intention, work family conflict had a 15.6% effect on turnover intention, job satisfaction and work family conflict had a 17.7% effect on turnover intention. Based on the results of partial hypothesis testing, job satisfaction had a negative effect on turnover intention, work family conflict had a positive effect on turnover intention. Based on the results of simultaneous hypothesis testing, job satisfaction and work family conflict had an effect on turnover intention.